BOPA : a bayesian hierarchical model for outlier expression detection - Hong, Zhaoping (2012)
DNA microarray technologies have the capability of simultaneously measuring the abundance of thousands of gene expressions in cells. A common task with microarrays is to determine which genes are differentially expressed under two different biological conditions of interest (e.g. cancerous against non-cancerous cells). It is often the case that there are thousands of genes for a single individual but relatively few individuals in the data set. Additionally, in many cancer studies, a gene may be expressed in some but not all